Pandemic Leadership: Sex Differences and Their Evolutionary–Developmental Origins - Luoto, Severi; Varella, Marco Antonio Correa (Frontiers in Psychology, 2021)
The COVID-19 pandemic has caused a global societal, economic, and social upheaval unseen in living memory. There have been substantial cross-national differences in the kinds of policies implemented by political decision-makers to prevent the spread of the virus, to test the population, and to manage infected patients. Among other factors, these policies vary with politicians’ sex: early findings indicate that, on average, female leaders seem more focused on minimizing direct human suffering caused by the SARS-CoV-2 virus, while male leaders implement riskier short-term decisions, possibly aiming to minimize economic disruptions. These sex differences are consistent with broader findings in psychology, reflecting women’s stronger empathy, higher pathogen disgust, health concern, care-taking orientation, and dislike for the suffering of other people—as well as men’s higher risk-taking, Machiavellianism, psychopathy, narcissism, and focus on financial indicators of success and status. This review article contextualizes sex differences in pandemic leadership in an evolutionary framework. Evolution by natural selection is the only known process in nature that organizes organisms into higher degrees of functional order, or counteracts the unavoidable disorder that would otherwise ensue, and is therefore essential for explaining the origins of human sex differences. Differential sexual selection and parental investment between males and females, together with the sexual differentiation of the mammalian brain, drive sex differences in cognition and behavioral dispositions, underlying men’s and women’s leadership styles and decision-making during a global pandemic. According to the sexually dimorphic leadership specialization hypothesis, general psychobehavioral sex differences have been exapted during human evolution to create sexually dimorphic leadership styles. They may be facultatively co-opted by societies and/or followers when facing different kinds of ecological and/or sociopolitical threats, such as disease outbreaks or intergroup aggression. Early evidence indicates that against the invisible viral foe that can bring nations to their knees, the strategic circumspection of empathic feminine health “worriers” may bring more effective and humanitarian outcomes than the devil-may-care incaution of masculine risk-taking “warriors”.